A carbon fiber flexible textile memristor based on titanium dioxide nanorod array and its preparation method
By adopting nitrogen-doped modified titanium dioxide nanorod array and carbon fiber cross structure in flexible electronic textiles, the problem that traditional flexible memristor devices are difficult to meet the needs of flexible electronic textiles is solved, and a flexible textile memristor with high efficiency and low power consumption is achieved.
Patent Information
- Application Number
- CN202410802226.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-20
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-06-20
AI Technical Summary
Traditional flexible memristor devices are difficult to meet the stringent requirements of flexible electronic textiles for flexibility, lightweight, breathability and complex deformation, especially in the preparation of stable and durable memristor layers on micron-sized fiber electrode surfaces.
A carbon fiber flexible textile memristor based on titanium dioxide nanorod array is used to increase the reaction rate and the formation of conductive wires through nitrogen doping, and N-TiO2@Cf and Al@Cf layers are prepared by hydrothermal method and magnetron sputtering coating technology to achieve cross-over overlap structure.
A flexible textile memristor with high switching ratio, low power consumption and high stability is achieved, which meets the needs of flexible electronic textiles and reduces costs through simple hydrothermal methods.
Smart Images

Figure CN118742195B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of memristor preparation, and in particular to a carbon fiber flexible textile memristor based on a titanium dioxide nanorod array and a preparation method thereof. Background Art
[0002] As a two-terminal non-electrical circuit device, memristor is regarded as an outstanding candidate for the next generation of non-volatile memory devices due to its low power consumption, high scalability, rapid response, excellent cyclability and non-volatility. It has shown broad application prospects in the fields of smart wearables, data storage, neural computing and storage-computing integration. Memristor consists of a sandwich structure consisting of a top electrode, a memristor functional layer and a bottom electrode, in which the electrode types are diverse, including active electrodes, inert electrodes and organic electrodes. The materials that realize the memristor function include oxides, sulfides, nitrides and organic substances, and their performance can be adjusted to the optimal state through clever doping and compounding methods.
[0003] With the rapid development of technologies such as the Internet of Things and the fifth generation of mobile communications, flexible memristor devices have emerged. They have energy storage, sensing and display functions, and have revolutionized the paradigm of human-computer interaction. At present, flexible memristor devices are mainly manufactured based on plastic substrates, such as polyimide, mica, stainless steel and textile fibers. In pursuit of higher functionality and human-computer compatibility, the research on flexible electronic textiles is becoming a frontier hotspot for wearable platforms. However, traditional flexible memristor devices mostly use rigid substrates and multi-layer structures for their processing devices, which makes it difficult to meet the stringent requirements of flexible electronic textiles for flexibility, lightness, breathability and complex deformation.
[0004] At this time, memristors with a cross-array structure have attracted widespread attention due to their efficient memory computing capabilities and inherent compatibility with textile interwoven structures. However, there are still many challenges in preparing a stable and durable memristor layer on the curved surface of a micron-sized fiber electrode. Traditional insulating textile fibers cannot be directly used as a conductive substrate for flexible electronic textiles, and carbon fibers, with their light weight, high strength, weavability, and good conductivity, have become an ideal choice for solving these problems. Through the application of carbon fibers, we hope to overcome technical difficulties and promote the development of textile flexible memristors, bringing revolutionary progress to wearable technology and human-computer interaction. TiO2, as an earlier studied memristor material, has rich memristive characteristics. And TiO 2- NRAs have a one-dimensional nanoarray structure, which is suitable for preparing nanoarray devices, and the preparation method is simple, and can be prepared by a simple one-step hydrothermal method, with low cost. The growth morphology of the nanorod array is closely related to the morphology of the conductive wire, and the growth morphology has a significant impact on the performance of the device. Therefore, the present invention provides a carbon fiber flexible textile memristor based on titanium dioxide nanorod array and a preparation method thereof. Summary of the invention
[0005] The purpose of the present invention is to provide a carbon fiber flexible textile memristor based on titanium dioxide nanorod array and a preparation method thereof, wherein aluminum-plated T700 carbon fiber is used as a top electrode, N-TiO2 is used as a functional layer, and T700 carbon fiber is used as a bottom electrode, wherein the N-TiO2 functional layer is plated on the bottom electrode. Nitrogen doping is used to increase the pressure of the reaction system, reduce the activation energy of the reaction system, and increase the reaction rate, resulting in an increase in the growth rate of the nanorods, causing TiO2 to produce more point defects, and at the same time increasing the nitrogen content of the internal lattice of TiO2. These defect structures excite vacancies under the action of an external electric field, and can form thicker conductive filaments, thereby regulating the defects and morphology of the Ti O2 layer.
[0006] To achieve the above objectives, the present invention provides a carbon fiber flexible textile memristor based on titanium dioxide nanorod array, which is formed by overlapping two mutually interlaced coated carbon fibers, and the two coated fibers are divided into top and bottom electrodes, the top electrode is T700 carbon fiber coated with aluminum, and the bottom electrode is T700 carbon fiber coated with an N-TiO2 functional layer.
[0007] The present invention also provides a method for preparing the above-mentioned carbon fiber flexible textile memristor based on titanium dioxide nanorod array, comprising the following steps:
[0008] 1) Prepare a dilute hydrochloric acid solution A by taking a certain amount of concentrated hydrochloric acid and deionized water, then drop a certain amount of tetrabutyl titanate into solution A, and stir to obtain a clear solution B; then add a certain amount of urea into solution B, and stir to obtain solution C;
[0009] 2) placing the solution C obtained in step 1) into a hydrothermal reactor and adding a section of T700 carbon fiber to perform a hydrothermal reaction to obtain a carbon fiber sample;
[0010] 3) Washing the carbon fiber sample obtained in step 2) and then drying it to obtain N-TiO2@C f ;
[0011] 4) The N-TiO2@C obtained in step 3) f Heat treatment is performed under an argon atmosphere;
[0012] 5) Place T700 carbon fiber and Al target into a magnetron sputtering coating machine, and obtain Al@C by RF magnetron sputtering. f .
[0013] 6) The fibers obtained in step 4) and step 5) are cross-jointed to obtain N-TiO2@C f / Al@C f Flexible textile memristor.
[0014] Preferably, in step 1), the volume ratio of concentrated hydrochloric acid to deionized water is (1-3):2, the volume ratio of tetrabutyl titanate to dilute hydrochloric acid solution A is (3-10):250, and the mass ratio of urea to solution B is (0-10):50.
[0015] Preferably, the temperature of the hydrothermal reaction in step 2) is 130° C. to 200° C., and the reaction time is 3 hours.
[0016] Preferably, the reagents used for washing in step 3) are deionized water and anhydrous ethanol, and the sample is first washed with deionized water for 3 to 4 times, and then washed with anhydrous ethanol for 2 to 3 times.
[0017] Preferably, the drying temperature in step 3) is 60° C. and the drying time is 10 h.
[0018] Preferably, in step 5), the RF magnetron sputtering time is 300 s, the magnetron sputtering power is 200 W, and the sputtering pressure is 0.2-1.0 Pa.
[0019] Therefore, the present invention provides a carbon fiber flexible textile memristor based on titanium dioxide nanorod array and a preparation method thereof, which has the following beneficial effects:
[0020] (1) The memristor is composed of aluminum-plated carbon fiber as the top electrode, N-TiO2 as the functional layer, T700 carbon fiber as the bottom electrode, and a rutile TiO2 nanorod array uniformly grown on the carbon fiber as the dielectric layer. Nitrogen doping increases the pressure of the reaction system, reduces the activation energy of the reaction system, and increases the reaction rate, resulting in an increase in the growth rate of the nanorods, causing more point defects in TiO2. At the same time, the nitrogen content in the internal lattice of TiO2 increases. These defect structures stimulate vacancies under the action of an external electric field and can form thicker conductive filaments. The vacancy content is controlled by the content of urea and the temperature of heat treatment, and the thickness of the titanium oxide coating is controlled by the content of urea and tetrabutyl titanate. The prepared N-TiO2 containing a large number of defects and thick conductive filaments has higher electron and ion migration efficiency, higher switching ratio and lower energy consumption.
[0021] (2) Preparation of N-TiO2@C f The method is to use urea nitriding on the basis of hydrothermal method to synthesize N-TiO2 with different morphologies on carbon fiber, and finally improve the N-TiO2 crystal form and regulate N-TiO2 defects by heat treatment.
[0022] (3)Al@C f It is deposited on T700 carbon fiber by magnetron sputtering. f With Al@C f The overlapped flexible textile memristor has the advantages of higher switching ratio and stability, lower power consumption, etc.
[0023] (4) The hydrothermal method for preparing the flexible textile memristor is simple, low-cost, and can control the morphology, thereby regulating the defects and morphology of the TiO2 layer.
[0024] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the structure of the carbon fiber cross-programmable memristor;
[0026] Figure 2 This is the SEM surface image of the nitrogen-doped modified titanium oxide nanorod coating of Comparative Example 2;
[0027] Figure 3 This is the SEM surface image of the nitrogen-doped modified titanium oxide nanorod coating of Example 1;
[0028] Figure 4 This is the SEM surface image of the nitrogen-doped modified titanium oxide nanorod coating of Comparative Example 3;
[0029] Figure 5 This is the XRD pattern of the nitrogen-doped modified titanium oxide nanorod coating after heat treatment at 200°C in Comparative Example 1;
[0030] Figure 6 This is the XRD pattern of the nitrogen-doped modified titanium oxide nanorod coating after heat treatment at 300° C. in Example 1;
[0031] Figure 7 This is the XPS image of the nitrogen-doped modified titanium oxide nanorod coating of Example 1;
[0032] Figure 8 This is a high-resolution XPS image of Ti 2p of the nitrogen-doped modified titanium oxide nanorod coating in Example 1;
[0033] Fig. 9 is the IV cycle curve of the device obtained in Comparative Example 1;
[0034] Fig.10 This is the IV cycle curve of the device obtained in Comparative Example 2;
[0035] Fig.11 This is the IV cycle curve of the device obtained in Comparative Example 3;
[0036] Fig.12 This is the IV cycle curve of the device obtained in Comparative Example 4;
[0037] Fig.13 This is the IV cycle curve of the device obtained in Example 1. DETAILED DESCRIPTION
[0038] The present invention provides a carbon fiber flexible textile memristor based on titanium dioxide nanorod array, the structure of which is as follows: Figure 1 As shown, the aluminum-plated T700 carbon fiber is used as the top electrode, N-TiO2 is used as the functional layer, and the T700 carbon fiber is used as the bottom electrode, wherein the N-TiO2 functional layer is plated on the bottom electrode. Nitrogen doping increases the pressure of the reaction system, reduces the activation energy of the reaction system, increases the reaction rate, and leads to an increase in the growth rate of nanorods, causing more point defects in TiO2, and increasing the nitrogen content in the TiO2 internal lattice. These defect structures stimulate vacancies under the action of an external electric field, which can form thicker conductive filaments.
[0039] The present invention also provides a method for preparing a carbon fiber flexible textile memristor based on a titanium dioxide nanorod array, comprising the following steps:
[0040] 1) Weigh a certain amount of concentrated hydrochloric acid and deionized water respectively, mix them evenly to obtain a dilute hydrochloric acid solution A. Use a pipette to weigh a certain amount of tetrabutyl titanate, slowly add it dropwise to solution A, and stir it for a while to obtain a clear solution B. Weigh a certain amount of urea, slowly add it to solution B, and stir it continuously for a while to obtain solution C.
[0041] 2) The solution C obtained in step 1) is placed in a hydrothermal reactor and a section of T700 carbon fiber is added to perform a hydrothermal reaction to obtain a carbon fiber sample.
[0042] 3) Washing the carbon fiber sample obtained in step 2) and then drying it to obtain N-TiO2@C f .
[0043] 4) The N-TiO2@C obtained in step 3) f N-TiO2@C with optimized performance was obtained after heat treatment in argon atmosphere. f .
[0044] 5) Place T700 carbon fiber and Al target into a magnetron sputtering coating machine, and obtain Al@C by RF magnetron sputtering. f .
[0045] 6) The fibers obtained in step 3) and step 5) are cross-jointed to finally obtain N-TiO2@C f / Al@C f Flexible textile memristor.
[0046] In the present invention, the volume ratio of concentrated hydrochloric acid to deionized water is (1-3):2, the volume ratio of tetrabutyl titanate to dilute hydrochloric acid is (3-10):250, and the mass ratio of urea to solution B is (0-10):50.
[0047] In the present invention, the temperature of the hydrothermal reaction is 130° C. to 200° C., and the time is 3 hours.
[0048] In the present invention, the reagents used for washing are deionized water and anhydrous ethanol, and the substrate needs to be washed 3 to 4 times with deionized water and then washed 2 to 3 times with anhydrous ethanol.
[0049] In the present invention, the drying temperature is 60° C. and the drying time is 10 h.
[0050] In the present invention, the RF magnetron sputtering time is 300s, the magnetic sputtering power is 200W, and the sputtering pressure is 0.2-1.0Pa.
[0051] The technical solution provided by the present invention is described in detail below in conjunction with the embodiments, but the detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] Example 1
[0053] 1) Weigh 12.5 ml of concentrated hydrochloric acid and 12.5 ml of deionized water respectively, mix well to obtain dilute hydrochloric acid solution A. Use a pipette to weigh 1.7 ml of tetrabutyl titanate, slowly dropwise add to solution A, and stir thoroughly for a period of time to obtain a clear solution B. Weigh 5 g of urea, slowly add to solution B, and stir continuously for a period of time to obtain solution C.
[0054] 2) The solution C obtained in step 1) is placed in a hydrothermal reactor and a piece of T700 carbon fiber is added to perform a hydrothermal reaction at 150° C. to obtain a carbon fiber sample.
[0055] 3) Washing the carbon fiber sample obtained in step 2) and then drying it to obtain N-TiO2@C f .
[0056] 4) The N-TiO2@C obtained in step 3) f N-TiO2@C with optimized performance was obtained after heat treatment at 300℃ in argon atmosphere. f .
[0057] 5) Place T700 carbon fiber and Al target into a magnetron sputtering coating machine, and obtain Al@C by RF magnetron sputtering. f .
[0058] 6) The fibers obtained in step 3) and step 5) are cross-jointed to finally obtain N-TiO2@C f / Al@C fFlexible textile memristor.
[0059] The SEM image of the nitrogen-doped modified titanium oxide nanorod coating obtained in step 2) of this embodiment is as follows: Figure 3 As shown by Figure 3 It can be seen that the thickness of the N-TiO2 layer is moderate, indicating that the heat treatment temperature is appropriate.
[0060] The XPS image of the nitrogen-doped modified titanium oxide nanorod coating obtained in step 2) of this embodiment is as follows: Figure 7 As shown by Figure 7 It can be seen that Ti, O, and N elements were successfully plated on carbon fibers.
[0061] The Ti 2p high-resolution XPS image of the nitrogen-doped modified titanium oxide nanorod coating obtained in step 2) of this embodiment is as follows: Figure 8 As shown by Figure 8 It can be seen that the energy difference between the two Ti 2p splitting peaks is 5.8 eV, which is consistent with the range of divalent titanium oxide.
[0062] The XRD pattern of the nitrogen-doped modified titanium oxide nanorod coating obtained in step 4) of this embodiment is as follows: Figure 6 As shown by Figure 6 It can be seen that after heat treatment at 300°C, the characteristic peak intensity of rutile titanium oxide increases and the half-width becomes narrower, which means that the lattice size and crystallinity are improved.
[0063] The resistance switching performance of the memristor prepared in this embodiment was tested, and the results were as follows: Fig.13 As shown by Fig.13 It can be seen that the window is large and the on / off ratio is stable at 10 4 , and the memristor is bipolar, which can meet practical needs.
[0064] Comparative Example 1
[0065] 1) Weigh 12.5 ml of concentrated hydrochloric acid and 12.5 ml of deionized water respectively, mix well to obtain dilute hydrochloric acid solution A. Use a pipette to weigh 1.7 ml of tetrabutyl titanate, slowly dropwise add to solution A, and stir thoroughly for a period of time to obtain a clear solution B. Weigh 5 g of urea, slowly add to solution B, and stir continuously for a period of time to obtain solution C.
[0066] 2) The solution C obtained in step 1) is placed in a hydrothermal reactor and a piece of T700 carbon fiber is added to carry out a hydrothermal reaction at 150°C.
[0067] 3) Washing the carbon fiber sample obtained in step 2) and then drying it to obtain N-TiO2@C f .
[0068] 4) The N-TiO2@C obtained in step 3) fN-TiO2@C with optimized performance was obtained after heat treatment at 200 °C in an argon atmosphere. f .
[0069] 5) Place T700 carbon fiber and Al target into a magnetron sputtering coating machine, and obtain Al@C by RF magnetron sputtering. f .
[0070] 6) The fibers obtained in step 3) and step 5) are cross-jointed to finally obtain N-TiO2@C f / Al@C f Flexible textile memristor.
[0071] The XRD pattern of the nitrogen-doped modified titanium oxide nanorod coating obtained in step 4) of this embodiment is as follows: Figure 5 As shown by Figure 5 It can be seen that after heat treatment at 200° C., the characteristic peak intensity of rutile titanium oxide increases and the half-width becomes narrower, which means that the lattice size and crystallinity are improved, but the effect is not as good as that of Example 1.
[0072] The resistance switching performance of the memristor prepared in this comparative example is tested. The results are as follows: Fig. 9 As shown by Fig. 9 It can be seen that the memristor is bipolar, but the heat treatment temperature is insufficient, the crystal form is not stable enough, the window is small, and the switching ratio is small, which is not enough to meet actual needs.
[0073] Comparative Example 2
[0074] 1) Weigh 12.5 ml of concentrated hydrochloric acid and 12.5 ml of deionized water respectively, mix well to obtain dilute hydrochloric acid solution A. Use a pipette to weigh 1.7 ml of tetrabutyl titanate, slowly dropwise add it to solution A, and stir thoroughly for a period of time to obtain a clear solution B. Weigh 2.5 g of urea, slowly add it to solution B, and stir continuously for a period of time to obtain solution C.
[0075] 2) The solution C obtained in step 1) is placed in a hydrothermal reactor and a piece of T700 carbon fiber is added to carry out a hydrothermal reaction at 150°C.
[0076] 3) Washing the carbon fiber sample obtained in step 2) and then drying it to obtain N-TiO2@C f .
[0077] 4) The N-TiO2@C obtained in step 3) f N-TiO2@C with optimized performance was obtained after heat treatment at 200 °C in an argon atmosphere. f .
[0078] 5) Place T700 carbon fiber and Al target into a magnetron sputtering coating machine, and obtain Al@C by RF magnetron sputtering. f .
[0079] 6) The fibers obtained in step 3) and step 5) are cross-jointed to finally obtain N-TiO2@C f / Al@C f Flexible textile memristor.
[0080] The resistance switching performance of the memristor prepared in this comparative example is tested. The results are as follows: Fig.10 As shown, the surface morphology of N-TiO2 is Figure 2 As shown in the figure, it can be seen that due to the low concentration of urea added, the film is not completely coated with carbon fibers, resulting in a smaller window, a small switching ratio, and a bipolar memristor, which is insufficient to meet actual needs.
[0081] Comparative Example 3
[0082] 1) Weigh 12.5 ml of concentrated hydrochloric acid and 12.5 ml of deionized water respectively, mix well to obtain dilute hydrochloric acid solution A. Use a pipette to weigh 1.7 ml of tetrabutyl titanate, slowly dropwise add to solution A, and stir thoroughly for a period of time to obtain a clear solution B. Weigh 7.5 g of urea, slowly add to solution B, and stir continuously for a period of time to obtain solution C.
[0083] 2) The solution C obtained in step 1) is placed in a hydrothermal reactor and a piece of T700 carbon fiber is added to carry out a hydrothermal reaction at 150°C.
[0084] 3) Washing the carbon fiber sample obtained in step 2) and then drying it to obtain N-TiO2@C f .
[0085] 4) The N-TiO2@C obtained in step 3) f N-TiO2@C with optimized performance was obtained after heat treatment at 300℃ in argon atmosphere. f .
[0086] 5) Place T700 carbon fiber and Al target into a magnetron sputtering coating machine, and obtain Al@C by RF magnetron sputtering. f .
[0087] 6) The fibers obtained in step 3) and step 5) are cross-jointed to finally obtain N-TiO2@C f / Al@C f Flexible textile memristor.
[0088] The resistance switching performance of the memristor prepared in this comparative example is tested. The results are as follows: Fig.11 As shown, the surface morphology of N-TiO2 is Figure 4 As shown in the figure, it can be seen that if too much urea is added, the N-TiO2 layer is too thick, and the conductive filament is difficult to form, resulting in a smaller window, a small switching ratio, and the memristor is unipolar, which is not enough to meet actual needs.
[0089] Comparative Example 4
[0090] 1) Weigh 12.5 ml of concentrated hydrochloric acid and 12.5 ml of deionized water respectively, mix well to obtain dilute hydrochloric acid solution A. Use a pipette to weigh 1.7 ml of tetrabutyl titanate, slowly dropwise add to solution A, and stir thoroughly for a period of time to obtain a clear solution B. Weigh 7.5 g of urea, slowly add to solution B, and stir continuously for a period of time to obtain solution C.
[0091] 2) The solution C obtained in step 1) is placed in a hydrothermal reactor and a piece of T700 carbon fiber is added to carry out a hydrothermal reaction at 150°C.
[0092] 3) Washing the carbon fiber sample obtained in step 2) and then drying it to obtain N-TiO2@C f .
[0093] 4) The N-TiO2@C obtained in step 3) f N-TiO2@C with optimized performance was obtained after heat treatment at 400℃ in argon atmosphere. f .
[0094] 5) Place T700 carbon fiber and Al target into a magnetron sputtering coating machine, and obtain Al@C by RF magnetron sputtering. f .
[0095] 6) The fibers obtained in step 3) and step 5) are cross-jointed to finally obtain N-TiO2@C f / Al@C f Flexible textile memristor.
[0096] The resistance switching performance of the memristor prepared in this comparative example is tested. The results are as follows: Fig.12 As shown, due to the excessive addition of urea, the N-TiO2 layer is too thick and the conductive filament is difficult to form, resulting in a smaller window, a small switching ratio, and a unipolar memristor, which is not enough to meet actual needs.
[0097] In summary, as the amount of urea added increases, the hydrothermally synthesized TiO2 film becomes thicker and more uniform. The heat treatment optimizes the crystal form of N-TiO2, increases the vacancies of the film and stabilizes the performance of the film. According to the XRD results of the heat treatment at 200℃-400℃, the phase composition of N-TiO2 has not changed. The experiment found that the thickness of N-TiO2 brought by the addition of 5g of urea is moderate, and the heat treatment temperature of 300-400℃ can obtain a larger switching ratio and number of cycles.
[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a carbon fiber flexible textile memristor based on a titanium dioxide nanorod array, characterized in that: The memristor is formed by overlapping two mutually interlaced coated carbon fibers, the two coated fibers are divided into top and bottom electrodes, the top electrode is T700 carbon fiber coated with aluminum, and the bottom electrode is T700 carbon fiber coated with N-TiO2 functional layer; The preparation comprises the following steps: 1) Prepare a dilute hydrochloric acid solution A by taking a certain amount of concentrated hydrochloric acid and deionized water, then drop a certain amount of tetrabutyl titanate into solution A, and stir to obtain a clear solution B; then add a certain amount of urea into solution B, and stir to obtain solution C; 2) placing the solution C obtained in step 1) into a hydrothermal reactor and adding a section of T700 carbon fiber to perform a hydrothermal reaction to obtain a carbon fiber sample; 3) washing the carbon fiber sample obtained in step 2) and then drying it to obtain N-TiO2@C f ; 4) The N-TiO2@C obtained in step 3) f Heat treatment is performed at 300-400°C in an argon atmosphere; 5) Place T700 carbon fiber and Al target into a magnetron sputtering coating machine, and obtain Al@C by RF magnetron sputtering. f ; 6) The fibers obtained in step 4) and step 5) are cross-jointed to obtain N-TiO2@C f / Al@C f Flexible textile memristor; In the step 1), the volume ratio of concentrated hydrochloric acid to deionized water is (1-3):2, the volume ratio of tetrabutyl titanate to dilute hydrochloric acid solution A is (3-10):250, and the mass ratio of urea to solution B is (0-10):
50.
2. The method for preparing a carbon fiber flexible textile memristor based on titanium dioxide nanorod array according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step 2) is 130° C. to 200° C., and the reaction time is 3 hours.
3. The method for preparing a carbon fiber flexible textile memristor based on titanium dioxide nanorod array according to claim 1, characterized in that: The reagents used for washing in step 3) are deionized water and anhydrous ethanol. The washing is first performed with deionized water for 3 to 4 times, and then with anhydrous ethanol for 2 to 3 times.
4. The method for preparing a carbon fiber flexible textile memristor based on titanium dioxide nanorod array according to claim 1, characterized in that: The drying temperature of step 3) is 60° C. and the drying time is 10 h.
5. The method for preparing a carbon fiber flexible textile memristor based on titanium dioxide nanorod array according to claim 1, characterized in that: In the step 5), the RF magnetron sputtering time is 300 s, the magnetron sputtering power is 200 W, and the sputtering pressure is 0.2-1.0 Pa.
Citation Information
Patent Citations
Nitrogen-doped titanium dioxide array memristor and preparation method thereof
CN110137351A
Cu-coated MoS2-coated Cf / Cu-coated Cf flexible spinnable memristor and preparation method thereof
CN118102858A